2020
DOI: 10.1038/s41386-020-00875-6
|View full text |Cite
|
Sign up to set email alerts
|

The medial entorhinal cortex mediates basolateral amygdala effects on spatial memory and downstream activity-regulated cytoskeletal-associated protein expression

Abstract: The authors thank John Wemmie, Rong Fan, and Joshua Weiner for their excellent technical assistance and for allowing us to utilize their laboratory facilities for the experiments involving Western blotting.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 95 publications
0
5
0
Order By: Relevance
“…Therefore post-injury testing targeted the ability to recall a previously learned task. Second, mice completed the Barnes maze (Barnes et al, 1980), which is a hippocampal-dependent spatial memory task (McNaughton et al, 1986) that also engages other brain regions such as the basolateral amygdala and entorhinal cortex for memory consolidation (Wahlstrom et al, 2020). Third, mice completed fear conditioning which includes both hippocampaldependent and -independent components and is associated with cholinergic signaling (Gould and Wehner, 1999;Gale et al, 2001;Maren, 2003;Feiro and Gould, 2005;Pape and Pare, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore post-injury testing targeted the ability to recall a previously learned task. Second, mice completed the Barnes maze (Barnes et al, 1980), which is a hippocampal-dependent spatial memory task (McNaughton et al, 1986) that also engages other brain regions such as the basolateral amygdala and entorhinal cortex for memory consolidation (Wahlstrom et al, 2020). Third, mice completed fear conditioning which includes both hippocampaldependent and -independent components and is associated with cholinergic signaling (Gould and Wehner, 1999;Gale et al, 2001;Maren, 2003;Feiro and Gould, 2005;Pape and Pare, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…These data show that TBI does not induce gross pathological changes near the site of injury 17 weeks post-injury; however, other brain regions may be important in modulating behavioral recovery. For example, Barnes maze also engages other brain regions such as the basolateral amygdala and entorhinal cortex for memory consolidation (Wahlstrom et al, 2020). In addition, the hippocampus is required for the US-context association but the amygdala is required for the CS-US association (Kim and Fanselow, 1992;Phillips and LeDoux, 1992;Rudy, 1993;Gerlai, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Work from our laboratory found that stimulation of basolateral amygdala (BLA) cell bodies and BLA projections to other brain regions influenced memory consolidation in a frequency‐dependent manner—i.e., stimulation at a specific frequency produced memory enhancement or impairment not observed with other frequencies (Huff et al., 2016; Huff et al., 2013; Wahlstrom et al., 2018). Moreover, the stimulation frequency determined whether there were downstream alterations in synaptic plasticity‐associated proteins (Wahlstrom et al., 2021). A substantial body of literature supports the idea that specific neural rhythms or oscillations play a role in facilitating neural activity across structures important for memory and suggests the importance of these oscillations in memory consolidation (Bauer et al., 2007; Buzsaki, 2005; Buzsaki & Moser, 2013; Kanta et al., 2019; Popescu et al., 2009).…”
Section: Frequency Specificitymentioning
confidence: 99%
“…dCA3 outputs to the dCA1 have been implicated in contextual fear-memory reconsolidation 43 , and the dCA1 and BLA exhibit synchronized theta activity during fear-memory reconsolidation 44 . Some other relay regions between the dCA1 or the dCA1-dCA3 circuit and the BLA may include the ventral hippocampus 42,45,46 , entorhinal cortex 47,48 , and perirhinal cortex 42,49 , based on their connectivity with both the BLA and DH and their recognized involvement in memory reconsolidation in other paradigms.…”
Section: Reconsolidationmentioning
confidence: 99%